PENGARUH SIZE DAN AGE PADA TINGKAT UNDERPRICING SAHAM PERDANA DI BURSA EFEK INDONESIA - Permadi, Pande Kadek Ary Raditya; Wirama, Dewa Gede; Gayatri, Gayatri; Suaryana, I Gusti Ngurah Agung (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.11.TAHUN.2022DO - 10.24843/EEB.2022.v11.i11.p12, 2022)
The purpose of this study is to determine the stock price of companies whose IPOs have increased in the medium and long term, and also to determine the effect of size and age on the level of underpricing of initial shares on the Indonesia Stock Exchange. The population in this study were all companies that IPO on the Indonesia Stock Exchange in 2009 – 2017. The population in this study was 207 companies. The method of determining the sample selected is non-probability sampling with purposive sampling technique. Purposive sampling is a sampling technique with certain considerations, namely experiencing underpricing during the IPO and never being suspended or delisted during the observation period. The sample in this study were 171 companies. Analysis of the data used is multiple linear regression. The results of the descriptive analysis show that in the medium term the stock price has increased, while in the long term it has not increased. The results of the regression analysis show that size and age have a negative effect on underpricing in the medium term, while no effect in the long term.